Postgraduate students' perception on effective supervision: a case study at one public university in Malaysia - Zainal Abiddin, Norhasni (The Journal of International Social Research, 2007)
Universiti Putra Malaysia (UPM) is one of the Research Universities (RU) in Malaysia. In gaining RU status, a university must meet the criteria of a Research University. One of the criteria is that, RU must have quantity and quality of researcher including postgraduate students. Thus, the research done by postgraduate students could be used to enhance the quality of research through developing the knowledge in the field of study. Specifically, this research aims to identify the best practices relevant to effective supervision of postgraduate research students. This research done by the basis of qualitative approach which 12 postgraduate research students have been in-depth interviewed. The data have been analysed manually and there were eight themes derived from the interviews which could answered the research questions. The results have been successfully explored the experiences and respondents' perception towards effective supervision.